2004
DOI: 10.1179/acb.2004.014
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Light-Enhanced Visualization of Cutaneous Signs of Carotene and Vitamin a Dietary Deficiency

Abstract: Dietary deficiencies are multiple and some of them may induce specific changes in the skin biology and structure. Vitamin A deficiency is well identified as a cause of xerosis and follicular keratosis. Skin of the forehead and balding scalp was examined in 3 homeless alcoholic men who suffered from altered liver functions and denutrition including carotene and vitamin A deficiencies. The ultraviolet light-enhanced visualization (ULEV) method was used with a computer-assisted video camera equipped with an inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…This seemingly mutual exclusion has not yet received an explanation. These stereotyped dots of subclinical perifollicular melanoderma were described in a series of studies [5, 6, 8, 9, 10]. Recently, other authors have reported seemingly identical features and coined them peripilar signs [13]failing to relate them to the melanin load in the perifollicular epidermis.…”
Section: Ultraviolet-light-enhanced Visualizationmentioning
confidence: 97%
See 3 more Smart Citations
“…This seemingly mutual exclusion has not yet received an explanation. These stereotyped dots of subclinical perifollicular melanoderma were described in a series of studies [5, 6, 8, 9, 10]. Recently, other authors have reported seemingly identical features and coined them peripilar signs [13]failing to relate them to the melanin load in the perifollicular epidermis.…”
Section: Ultraviolet-light-enhanced Visualizationmentioning
confidence: 97%
“…1) can be revealed on the facial skin and scalp of some subjects [5, 6, 8, 9, 10]. They are almost never associated with enlarged empty funnel-shaped pores.…”
Section: Ultraviolet-light-enhanced Visualizationmentioning
confidence: 99%
See 2 more Smart Citations
“…This skin condition has many other origins [31] including vitamin A deficiency [32], climatic conditions [33], diabetes [34] and other endocrinopathies [5].…”
Section: Ancillary Effect Of Nutritional Deficiencymentioning
confidence: 99%